Analyzing the Influence of Mindfulness-Based Interventions on Mental Health: A Citation-Based Approach - Fitriah Handayani; jane Mariem Monepa; Ria Sulistiana; Melissa Silvana Patodo; Muhammad Nur Ikhsan Liwang (West Science Interdisciplinary Studies, 2023)
In recent years, mindfulness-based interventions, or MBIs, have drawn a lot of attention as a potentially effective strategy for enhancing mental health and wellbeing. In order to perform a bibliometric analysis of the literature on mental health and MBIs, this study looked at collaborative networks, prominent publications and authors, research themes, and patterns in research production. Notable discoveries include a notable increase in research production, with a spike in activity starting in the early 2000s, which reflects the growing acceptance of mindfulness in relation to mental health. The development of the area has been attributed to seminal publications, eminent writers, and interdisciplinary cooperation. The neurological underpinnings of mindfulness, stress reduction, and the management of anxiety and depression were the main research themes. These results highlight the value of MBIs in treating mental health issues and offer directions for further study and application.